A new approach for measuring the trabecular bone density through the echosound backscattering: An ex vivo validation on human femoral heads. (June 2016) - De Marco, Tommaso; Peccarisi, Marco; Conversano, Francesco; Greco, Antonio; Chiozzi, Samanta; De Pascalis, Fabio; Casciaro, Sergio
Highlights: A new ultrasound technique to estimate trabecular bone density was presented. Obtained results showed an appreciable correlation with micro-CT measurements. The proposed approach could become a method for in vivo measurement of bone density. Abstract: The aim of this paper was to propose a novel approach to the ultrasound (US) characterization of human bones through an improved measurement of the apparent integrated backscatter (AIB). Four intact human femoral heads were studied ex vivo in their physiologic morphological configuration, including cartilaginous, cortical and trabecular regions. Each sample underwent an US acquisition performed with a clinically-available echographic device and a micro-computed tomography (micro-CT) scan, whose spatial resolution was preliminarily optimized for this specific purpose. A dedicated US signal compensation was employed in the AIB computation, to take into account the variability of sample-probe distance and cortical bone thickness. Obtained results showed an appreciable global correlation between AIB and the trabecular bone volume fraction as quantified by the micro-CT parameter BV/TV (| r | = 0.69). The proposed approach has interesting perspectives for a clinical translation as an innovative method for in vivo US measurement of proximal femur bone density.